Absolute blood velocity measured with a modified fundus camera - Duncan, Donald D. (Society of Photo-Optical Instrumentation Engineers, 2010)
We present a new method for the quantitative estimation of blood flow velocity, based on the use of the Radon transform. The specific application is for measurement of blood flow velocity in the retina. Our modified fundus camera uses illumination from a green LED and captures imagery with a high-speed CCD camera. The basic theory is presented, and typical results are shown for an in vitro flow model using blood in a capillary tube. Subsequently, representative results are shown for representative fundus imagery. This approach provides absolute velocity and flow direction along the vessel centerline or any lateral displacement therefrom. We also provide an error analysis allowing estimation of confidence intervals for the estimated velocity.